Exploring the Relationship Between Mindfulness, Cognitive Flexibility, and Perceived Stress Among Adults - Aiman Aftab (Corresponding Author); Syeda Mahrukh Waqar; Ayesha Yashfeen (Journal of Religion and Society, 2025)
Stress is a common issue that affects physical health, emotional stability, and cognitive performance. Mindfulness, defined as non-judgmental present-moment awareness, plays a key role in lowering perceived stress and improving well-being. With an emphasis on gender differences, this study investigates the relationships among perceived stress, cognitive flexibility, and mindfulness. The Cognitive Flexibility Scale (CFS-12), Perceived Stress Scale (PSS-10), and Five Facet Mindfulness Questionnaire (FFMQ-39) were used in a cross-sectional study of 336 adults aged 18 years and older. Independent-samples t-tests examined gender differences, and Pearson correlation coefficients evaluated associations among mindfulness, cognitive flexibility, and perceived stress. Results showed a significant negative correlation between perceived stress and mindfulness (r = –0.233, p < 0.01), with mindfulness linked to reduced stress levels. Cognitive flexibility correlated positively with mindfulness (r = 0.164, p < 0.01) and weakly with perceived stress (r = 0.150, p < 0.01). Females reported higher perceived stress (M = 26.49, SD = 7.08) than males (M = 24.65, SD = 5.42), t(333) = –2.667, p = 0.008. Cognitive flexibility and mindfulness did not differ significantly by gender. Regression results further showed that mindfulness was a significant negative predictor of perceived stress (β = –.23, p < .001) and a significant positive predictor of cognitive flexibility (β = .16, p = .003). The findings highlight the importance of mindfulness and cognitive flexibility in reducing perceived stress and suggest that gender-specific approaches may enhance stress-management interventions. Keywords: Mindfulness, Cognitive Flexibility, Perceived Stress, Gender Differences, Psychological Well-being.